Efektivitas Pelayanan Menggunakan OPAC (Online Public Accses Catalog) Dalam Meningkatkan Aksesibilitas Informasi Bagi Masyarakat - Iwin Ardyawin; Cut Afrina (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
This research was conducted at the Central Lombok Regency Library and Archives Office, to know how the effectiveness of services using the OPAC (Online Public Access Catalog) application in improving information accessibility for the community and inhibiting factors in using the OPAC (online public access catalog) application. The method used in this study is quantitative with a descriptive type of research. The data collection techniques used are interviews, observations, and documentation. The data analysis technique used is the analysis flow model technique. To support this research, there are seven research steps used by researchers, namely (1) compiling a research design (2) Choosing a research field (3) Managing to license (4) Exploring and assessing the field (5) Choosing and utilizing informants (6) Preparing research equipment (7) Research ethics issues. One of the efforts made by the Central Lombok library to increase the level of visits and reading interest of the people of Central Lombok is the existence of OPAC or online catalogs that will provide convenience for users and staff in cataloging or searching for collections. The electronic catalog is also proven to be able to promote the collections in the library of central Lombok regency. So that the existing obstacles are of concern to the government, especially the library and archives office of central Lombok regency so that public interest in accessing information increases.